(3TQM GdOQ GdjJjes - (3CMeO aGFR GdQhei CafOis; (3GdHQcdj , eMjj GdOjf eMeO Hf HjQYdj Hf GScfOQ GdHQcdj GdQhej,J (B981 (3g` s
(3ChdgG (B:s
(3hHYO aEf Chdi eG jJhSd Hg Edi fjd GdZaQGf hCMQi eG jJhUd Hg Edi ONhd GdLfGf bQCI cJGH Gddg GdPi gh CHgQ MLL bQCfkG YQHjkG ZjQ Pi YhL s
(3BNQgG (B:s
(3hai GdKGdK bhdg JYGdi Edi Pdc Gdjhe GdMb ajLH GdJMaX Yf Pdc cdg Gddge GQRbfG GdYUeI Yf GdNWGA hGdNdd Je GdcJGH s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B61 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B123 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B252s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B737s
Keywords: (3GdbQGAGJ hGdJLhjOs